2007
DOI: 10.1007/s11060-006-9316-9
|View full text |Cite
|
Sign up to set email alerts
|

Promoter hypermethylation profile of cell cycle regulator genes in pituitary adenomas

Abstract: Aberrant hypermethylation of CpG islands in the promoter region plays a causal role in the inactivation of various key genes involved in the cell cycle regulatory cascade, which could result in a loss of cell cycle control. The aim of the present study was to examine in more detail the prevalence and role of the promoter methylation of genes with a proven involvement in the cell cycle regulation of pituitary adenomas, since their tumorigenesis has not yet been clearly defined. We profiled the CpG island methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
54
0
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 55 publications
0
54
0
5
Order By: Relevance
“…A detailed analysis suggested that CDKN2A methylation was confined to particular adenoma subtypes (Simpson et al 1999) and these findings were subsequently confirmed by several other groups concluding that hypermethylation of the CDKN2A is the most common epigenetic deregulation in these neoplasias (Morris et al 2005, Ogino et al 2005, Yoshino et al 2007 INK4a is able to inhibit cell proliferation in pituitary tumor cells in correlation with a shift in the phosphorylation status of pRB, suggesting the relevance of this CDK inhibitor in the activation of pRB and pituitary tumor suppression (Frost et al 1999).…”
Section: Ink4 Inhibitorsmentioning
confidence: 81%
See 1 more Smart Citation
“…A detailed analysis suggested that CDKN2A methylation was confined to particular adenoma subtypes (Simpson et al 1999) and these findings were subsequently confirmed by several other groups concluding that hypermethylation of the CDKN2A is the most common epigenetic deregulation in these neoplasias (Morris et al 2005, Ogino et al 2005, Yoshino et al 2007 INK4a is able to inhibit cell proliferation in pituitary tumor cells in correlation with a shift in the phosphorylation status of pRB, suggesting the relevance of this CDK inhibitor in the activation of pRB and pituitary tumor suppression (Frost et al 1999).…”
Section: Ink4 Inhibitorsmentioning
confidence: 81%
“…Cip1 are not commonly observed, this inhibitor may also be downregulated through epigenetic modifications in pituitary neoplasias (Yoshino et al 2007, Zhu et al 2008.…”
Section: Cip/kip Inhibitorsmentioning
confidence: 99%
“…INK4A by methylation is frequent in pituitary, mainly NFPA (Woloschak et al 1997, Simpson et al 1999a, Morris et al 2005, Ogino et al 2005, Yoshino et al 2007). Downregulation of p27 kip1 protein expression, likely due to a JAB1-mediated increased proteolysis (Korbonits et al 2002), is frequent in pituitary carcinomas and ACTH-secreting adenomas (Bamberger et al 1999, Lidhar et al 1999.…”
Section: The Cell Cyclementioning
confidence: 99%
“…Hyper-methylation of the promoter region also accounts for the loss of p16 INK4 protein expression, which is relatively frequent in PA (Simpson et al, 1999). RB and p16 INK4a methylations tended to be mutually exclusive (Yoshino et al, 2007).…”
Section: Cell Cycle Inhibitorsmentioning
confidence: 99%
“…As for pRB and p16 INK4a , down-regulation of p21 Cip1 and p27 kip1 in pituitary adenomas may also be due to epigenetic modifications, including DNA and/or histone methylation (Yoshino et al, 2007, Zhu et al, 2008.…”
Section: Cell Cycle Inhibitorsmentioning
confidence: 99%